IDENTIFYING GAPS AND NEEDS IN ENGLISH TEACHING PRACTICES FOR EFFECTIVE IMPLEMENTATION OF THE KURIKULUM MERDEKA AT SMPN 6 SENGAH TEMILA - Marsella, Dea; Hafis, Malikul; Sahrawi (Melekliterasi Press, 2025)
this research aims to identify the gaps and needs in English teaching practices at SMPN 6 Sengaja Temila. This research employs a case study design with a qualitative approach. Interviews, observations and documentation were used to collect data. The findings indicate that the gaps in the implementation of the kurikulum Merdeka incluade teachers' limited understanding and skill in teaching, such as difficulties in applaying appropiate methods and utilizing technology in their instruction, low student engagement in learning, lack of resource and facilities and challenges in conducting effective assessment. The identified needs in English teaching include the needs for advanced skills and further training related to the kurikulum Merdeka, as well as the need for the edaquate resource, facilities and infrastcture. This research contributes to teacher, principal, and governmant by providing insight to enhance the effectiveness of the kurikulum Merdeka implementation in English teaching at SMPN 6 Sengah Temila.